The Gold Content of Interflow Metasedimentary Rocks in the Red Lake Area - Cowan, Patricia (My University, 1979)
The two main groups of rocks studied were the sedimentary and volcanic rocks from the Red Lake area of the Uchi greenstone belt, northwestern Ontario. The objective of the study is to characterize the interflow sedimentary rocks in the volcanic pile with respect to gold content and to assess their significance in the gold metallogeny of the Red Lake gold camp. A suite of interflow sediments from the Dickenson mine was studied for comparison with the regional survey. The interflow sedimentary rocks studied were chert, mixed clastic and chemical sediments and iron formation, the latter including oxide, silicate, sulphide and mixed silicate-oxide. The chemical and petrographic features of these are summarized in Tables 2 and 3. The range of gold values is 0.4 to 360 ppb. The gold value for the oxide and sulphide iron formation was substantially higher than the rest of the interflow sediments. Only three samples of sulphide iron formation were sampled, so no definite conclusion can be made about it. The metavolcanic rocks range from komatiites to tholeiites to calc-alkaline rhyolites. The chemical and petrographic features are summarized in Table 4 and 5. The majority of samples collected were komatiites and tholeiites. The gold values range from 0.1 - 380 ppb. The high iron and high magnesium tholeiites contain higher gold values than the rest of the volcanics. Only three high magnesium tholeiites were sampled so that no definite gold trends can be ascertained for them. The Dickenson mine samples are characterized by interflow sediments containing both clastic and chemical components. The gold values range from 3.1 to 15100 ppb. The regional background value for gold is 3.5 ppb. Gold enrichment occurs in elongate zones parallel to the strike of the area. In general, high gold values in interflow sediments (>10 ppb) are accompanied by high gold values in volcanic rocks in the same vicinity. The gold enrichment is not characterized by any type of chemical anomaly. The model of gold formation proposed for the Red Lake area is that of primary enrichment of gold caused by either exhalative sources or seawater leaching of the underlying volcanics. Gold was deposited near the seawater-rock interface due to decreasing temperature and perhaps changes in Fo₂ and pressure. Gold may be further mobilized into shear and dilatent zones during metamorphism. The intrusion of stocks acts as a heat source to localize gold on the edges of these bodies.
Keywords: Geology; Geology